Survival of vine mealybug, Planococcus ficus (Signoret) (Hemiptera: Pseudococcidae), on grapevine root remnants in soil in the Western Cape Province, South Africa - Allsopp, E.; Fourie, J.C. (South African Journal of Enology and Viticulture, 2019)
Grapevine leafroll is the most damaging grapevine virus disease in South Africa, and the primary vector of Grapevine leafroll-associated virus 3 (GLRaV-3) is vine mealybug, Planococcus ficus (Signoret). Preventing re-infection of newly planted, virus-free grapevines is critical to control and prevent the spread of leafroll disease. Results from a previous survey raised concern that mealybugs surviving on leafroll-infected root remnants in the soil could transmit the virus to newly planted grapevines. This study aimed to determine if P. ficus commonly occurs on grapevine roots in the Western Cape Province of South Africa, if and for how long it can survive on remnant roots in soil, and if it can transmit GLRaV-3 to healthy grapevines after surviving on remnant roots. Surveys to determine the occurrence of mealybugs on grapevine roots were conducted at different times of the growing season in vineyards near Robertson, McGregor, Montagu, Somerset West and Malmesbury over three seasons. A field trial was conducted on a sand-clay-loam soil with 23% clay and a sandy-loam soil with 10% clay over 12 months to determine survival of different life stages of vine mealybug confined on root sections from leafroll-infected Pinotage/R110 grapevines. Results indicate that P. ficus does not readily occur on grapevine roots in the Western Cape, and that it does not survive well on root remnants of grapevines for any length of time. Implications for planting virus-free grapevines in soil where leafroll-infected vines were removed, are discussed.